The effect of fish oil versus krill oil intervention on clinical symptoms and cardiometabolic risk factors in patients with major depressive disorder: A randomized placebo-controlled double-blind trial - Acik, Murat; Cakiroglu, Funda Pinar; Tekin, Atilla; Egeli, Asli (Elsevier, 2025)
Background: This study aimed to compare the effects of krill- and fish-oil interventions on clinical symptoms and metabolic risk factors in individuals with MDD. Methods: In this randomized study, 57 adults diagnosed with MDD were allocated to receive krill-oil (520 mg EPA + DHA), fish-oil (600 mg EPA + DHA), or a placebo (soybean-oil) daily for 8 weeks. Anthropometric measurements, depression anxiety stress-21 (DASS-21) scale, and Hamilton depression rating scale (HDRS) were performed at baseline and 4 and 8 weeks. In addition, venous blood samples were collected at baseline and postintervention to evaluate lipid and glycemic profiles, including fasting glucose, HbA1c, cholesterol, triglycerides, LDL-c, and HDL-c levels.SPSS and R Studio software programs were used for statistical analysis. Results: A total of 50 participants completed the study, with 17 in each intervention group and 16 in the placebo. The mean HDRS scores decreased significantly in both the krill-oil (8.5 +/- 1.2) and fish-oil groups (10.0 +/- 1.2) compared to the placebo (p < 0.001), indicating clinical symptom improvement. Furthermore, the interaction effect of group-by-time was found to be statistically significant (eta 2p = 0.273;ptimexgroup < 0.001). Anxiety and distress scores decreased to similar levels after the post-intervention compared to baseline in krill- and fish-oil groups. Krill- and fish-oil supplementation increased plasma HDL-c and uric acid levels, but the group-by-time interaction effect was only observed at the HDL-c level (eta 2p = 0.238;ptimexgroup = 0.002). The mean HbA1c rates and plasma triglyceride levels of krill-oil recipients were lower after the post-intervention. Conclusion: Krill- and fish-oil could be considered as a safe and effective adjuvant treatments for depression. However, there was no evidence of apparent superiority over each other.
Keywords: Depression; N-3 PUFAs; Anxiety; Distress; Metabolic risk factors